The concepts of «medical care» and «medical service»: a civil-legal analysis - I. V. Ponkin (Акушерство, гинекология и репродукция, 2022)
The article is devoted to investigate and interpret the contents and correlation for the concepts of "medical care" and "medical service" in the context of public healthcare. Here, we demonstrate the defective features of the Russian legislation regarding accepting the necessary legal definitions for such concepts. At the same time, while performing a comprehensive formal legal analysis and applying interpretation by analogy, we provide generalizations allowing to understand the essence of the concepts analyzed as well as their inter-relationship. We interpret two definitions for the concept of "medical service", and envision that medical care vs. medical service is an ontological unit of a more general and higher level. Understanding the differences in the definitions of "medical care" and "medical service", demonstrated in the article, will be useful to healthcare organizers.